2008
DOI: 10.1111/j.1095-8649.2007.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of swimming performance in rainbow trout using constant acceleration and critical swimming speed tests

Abstract: Maximum swimming performance of seasonally acclimated rainbow trout Oncorhynchus mykiss was compared among short-duration constant acceleration tests (U max ) and with the well established, but longer duration critical swimming speed (U crit ) test. The present results show that U max was insensitive to a range of acceleration rates that differed by more than three-fold. Thus, test duration could be reduced from 58 to 18 min without affecting the estimate of U max . The value of U max , however, was up to 57% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
103
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 66 publications
2
103
0
Order By: Relevance
“…With regarding to the CSS, the influence of time intervals and velocity increments on its result has caught many atten-tions [22,27]. However, it still cannot draw a general conclusion on how the testing protocols will affect the final values of the CSS.…”
Section: Influence Of Testing Protocols On Fish Swimming Performancementioning
confidence: 99%
See 4 more Smart Citations
“…With regarding to the CSS, the influence of time intervals and velocity increments on its result has caught many atten-tions [22,27]. However, it still cannot draw a general conclusion on how the testing protocols will affect the final values of the CSS.…”
Section: Influence Of Testing Protocols On Fish Swimming Performancementioning
confidence: 99%
“…However, controversy has existed for a long time with respect to the influences of time interval and velocity increment on the CSS. Some authors demonstrated that there are no significant differences in the CSS with different protocols [27,28], while some authors found that the influence on the CSS is quite notable [29][30][31]. Also some authors argued that the influence on the CSS can be neglected within a certain range of time interval and velocity increment [7,22].…”
Section: Unsteady Swimming Performancementioning
confidence: 99%
See 3 more Smart Citations